Peran Sukuk Negara Dalam Pembangunan Infrastruktur di Indonesia - Raharjo Raharjo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Infrastructure development is one of the top priorities for the Indonesian government to achieve sustainable economic growth and enhance the quality of life for its people. Infrastructure plays a significant role in driving economic growth, as the availability of adequate infrastructure in a region contributes to the economic development of that area. However, it's acknowledged that financing large-scale and complex infrastructure projects requires substantial funds. Currently, government sukuk has become a popular choice for the Indonesian government to obtain funds aimed at financing infrastructure development. Economic growth serves as one of the indicators to assess the outcomes of past development efforts and determine the direction of future development. In other words, positive economic growth indicates an improvement in the economy, while negative economic growth signifies a decline. Funding sourced from foreign debt and infrastructure project development in Indonesia has consistently been a recurring issue over the years, given their interconnected nature. The government has taken various measures to ensure infrastructure continues to progress without adding to the burden of foreign debt for the country. One suitable option that can serve as a way out of the limitations in funding sources is through the issuance of Shariah Sovereign Securities or SBSN by the government.